2012
DOI: 10.1021/cm3002404
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Low-Temperature Epitaxy of Ge-based Semiconductors and Optoelectronic Structures on Si(100): Introducing Higher Order Germanes (Ge3H8, Ge4H10)

Abstract: This paper reports the development and optimization of an enhanced process to produce viable quantities of trigermane, and controlled smaller quantities tetragermane, which are isolated as a mixture of perfectly stable isomers. The identity and fundamental structural properties of these higher order germanes (Ge3H8, and Ge4H10 isomers) are thoroughly characterized using spectroscopic methods and quantum chemical simulations. These hydride products are found to exhibit a remarkably good stability and “ease of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 28 publications
4
44
2
Order By: Relevance
“…[4,5] Drawn by this challenge and the uncertainty associated with the structures of the metastable halides (SiCl 2 ) n and (GeCl 2 ) n in the solid state, [6] we focused our efforts towards developing an efficient bottom-up synthesis of related oligomers and polymers (ECl 2 ) x (x ! [8] In pursuit of this goal, we herein report the mild and sequential synthesis of Lewis base supported germanium dichloride oligomers (GeCl 2 ) x (x ! This strategy is predicated on the propensity of strong electron-pair donors to bind/stabilize SiCl 2 and GeCl 2 in the form of stable molecular adducts LB·ECl 2 (E = Si and Ge).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[4,5] Drawn by this challenge and the uncertainty associated with the structures of the metastable halides (SiCl 2 ) n and (GeCl 2 ) n in the solid state, [6] we focused our efforts towards developing an efficient bottom-up synthesis of related oligomers and polymers (ECl 2 ) x (x ! [8] In pursuit of this goal, we herein report the mild and sequential synthesis of Lewis base supported germanium dichloride oligomers (GeCl 2 ) x (x ! This strategy is predicated on the propensity of strong electron-pair donors to bind/stabilize SiCl 2 and GeCl 2 in the form of stable molecular adducts LB·ECl 2 (E = Si and Ge).…”
mentioning
confidence: 99%
“…Our efforts to install hydride functionality onto the Ge chain in 2 (to form germanium polyhydrides and/or clusters) [8,20] by treatment with Li[BH 4 ] led to the formation of IPr·GeH 2 ·BH 3 [10a] and germanium metal. The detailed mechanism of this transformation is unknown at this time, but our preliminary theoretical investigations (see below) suggest that isomerization of 2 to form related species, such as the linear isomer IPr·(GeCl 2 ) 4 , might be feasible.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13. We used 4 inch Ge(100) substrates with nominal thickness of 150-μm, miscut by 6 • toward (111) and doped p-type at levels of 6 × 10 17 cm −3 .…”
Section: Q174mentioning
confidence: 99%
“…However, recent advances in the study of Ge hydrides that contain more than two Ge centers have suggested new possibilities for the development of Ge chemistry 2730. In particular, Kouvetakis and co‐workers demonstrated the utility of trigermane (all‐Ge analogue of propane) and tetragermane (all‐Ge analogue of n ‐butane and isobutane) as precursors for semiconducting materials 28. Ge 4 H 4 not only serves as a computationally tractable model system for large molecules that contain Ge 4 motifs, but also deserves attention as a potential intermediate in synthetic procedures that employ larger Ge hydrides.…”
Section: Introductionmentioning
confidence: 99%